Learning eco-friendly food choice using extended reality – an exploratory investigation - Dobricki, Martin; Rihs, Michael; Shahmoradi, Sina (Frontiers in Virtual Reality, 2025)
IntroductionIt has not yet been investigated whether virtual reality (VR) may be useful to support the learning of eco-friendly food choice by enabling human individuals to experience motivational behavior-environment associations that depending on the carbon footprint of their food choice affect them negatively or positively. It is, accordingly, an open question if the viewer-including environment of VR can serve for this purpose better than a viewer-excluding PC version of it. We have, therefore, started to investigate this potential utility of VR in an exploratory investigation on the level of lower secondary education.MethodsFor this purpose, we have developed both a VR and a PC version of a task involving the following experience: the problem that choosing environmentally harming food with a high carbon footprint is accompanied by climate-related environmental alterations that are affecting oneself negatively can be solved by replacing this food with eco-friendly food with a low carbon footprint, which is accompanied by a reversal of such environmental alterations that is affecting oneself positively. In a first experiment, we have asked experienced lower secondary school teachers to test both the VR and PC version of our task and to rate its usefulness to teach eco-friendly food choice. In a second experiment we have subsequently started to explore the learning curve of lower secondary school children accomplishing either the VR or the PC version of the task by measuring their times to solve the problem involved in the task three consecutive times.ResultsIn the first experiment the teachers regarded the VR version of the task to be more useful for teaching eco-friendly food choices than its PC version. In accordance with this finding, in the second experiment the children were learning to solve the problem involved in the task more rapidly using its VR version than using its PC version.DiscussionHence, our findings converge in suggesting the following: experiencing motivational behavior-environment associations that depending on the carbon footprint of one’s food choice affect oneself negatively or positively using the VR version of our task may serve better to support the learning of eco-friendly food choice than using its PC version.